2016
DOI: 10.1086/685016
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interaction of Riociguat with Ketoconazole, Clarithromycin, and Midazolam

Abstract: Riociguat is a soluble guanylate cyclase stimulator for the treatment of pulmonary hypertension that is principally metabolized via the cytochrome P450 (CYP) pathway. Three studies in healthy males investigated potential pharmacokinetic interactions between riociguat and CYP inhibitors (ketoconazole, clarithromycin, and midazolam). In two studies, subjects were pretreated with either once-daily ketoconazole 400 mg or twice-daily clarithromycin 500 mg for 4 days before cotreatment with either riociguat 0.5 mg ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 10 publications
6
31
0
Order By: Relevance
“…16,17 The pharmacokinetic properties of riociguat in the current studies were generally similar to previous clinical pharmacology studies of riociguat administered to healthy volunteers in a fasted state (AUC and C max for riociguat 1.0-mg whole IR tablet of 171-244 μg h/L and 20.8-37.8 μg/L, respectively, in previous studies, compared with 311 μg h/L and 35.8 μg/L, respectively, in the current studies). 18,19 Furthermore, the comparable bioavailability of the different formulations of riociguat in the current studies is consistent with previous studies that have shown no relevant differences in bioavailability between riociguat administered as a 2.5-mg whole 6-mmdiameter tablet or as a 2.5-mg solution 20 or riociguat administered as an oral 1.0-mg whole 6-mm tablet and as a 1.0-mg intravenous infusion. 18 The apparent interchangeability of riociguat administered as a whole IR tablet, oral suspension, or crushed IR tablet suspended in applesauce or water provides the potential to consider riociguat as a treatment option in eligible patient populations unable to swallow whole 6-mm-diameter tablets.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…16,17 The pharmacokinetic properties of riociguat in the current studies were generally similar to previous clinical pharmacology studies of riociguat administered to healthy volunteers in a fasted state (AUC and C max for riociguat 1.0-mg whole IR tablet of 171-244 μg h/L and 20.8-37.8 μg/L, respectively, in previous studies, compared with 311 μg h/L and 35.8 μg/L, respectively, in the current studies). 18,19 Furthermore, the comparable bioavailability of the different formulations of riociguat in the current studies is consistent with previous studies that have shown no relevant differences in bioavailability between riociguat administered as a 2.5-mg whole 6-mmdiameter tablet or as a 2.5-mg solution 20 or riociguat administered as an oral 1.0-mg whole 6-mm tablet and as a 1.0-mg intravenous infusion. 18 The apparent interchangeability of riociguat administered as a whole IR tablet, oral suspension, or crushed IR tablet suspended in applesauce or water provides the potential to consider riociguat as a treatment option in eligible patient populations unable to swallow whole 6-mm-diameter tablets.…”
Section: Discussionsupporting
confidence: 91%
“…As expected, the most common adverse events (headache, nausea, dizziness, and nasal obstruction/congestion) were consistent with the vasodilatory action of riociguat. The safety profile was consistent with previous studies of riociguat in healthy volunteers [18][19][20] and in patients with PAH or CTEPH 10 and provides further evidence for the safety and tolerability of riociguat treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Riociguat and M1 are neither inhibitors nor inducers of major CYP isoforms (including CYP3A4) in vitro at therapeutic plasma concentrations, as also shown in an earlier clinical interaction study with the sensitive CYP3A4 substrate midazolam, in which no change in exposure was observed. 15 The lack of effect on CYP isoforms may explain the absence of a significant PK interaction in this study. Riociguat exposure was not influenced by coadministration with levonorgestrel-ethinylestradiol.…”
Section: Discussionmentioning
confidence: 76%
“…The fractions metabolized via CYP1A1 and CYP3A4 for riociguat were estimated by revisiting data from clinical DDI studies [48] with clarithromycin (a strong CYP3A4 and P-gp inhibitor) [49,50] and with ketoconazole (a strong CYP3A4, strong CYP1A1, and P-gp inhibitor) [51,52]. Concomitant administration of ketoconazole 400 mg led to a 46% increase in C max of riociguat and a 150% increase in AUC.…”
Section: Estimation Of Fraction Metabolized (F M ) For Cyp1a1 and Cyp3a4mentioning
confidence: 99%